Pengaruh Opini Audit, Ukuran Kantor Akuntan Publik, Ukuran Perusahaan, dan Profitabillitas terhadap Audit Delay: The Influence of Audit Opinion, Public Accounting Firm Size, Company Size, and Profitability on Audit Delay - Siti Mahromyah, Irma; Rismayani, Gista; Khodijah, Amalia Siti (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2025)
This study aims to analyze the factors influencing audit delay in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Audit delay is a crucial issue as it reflects the timeliness, transparency, and accountability of publicly listed companies in disclosing their financial information. This research employs a quantitative approach using multiple linear regression analysis to examine the effects of audit opinion, firm size, public accounting firm (PAF) size, and profitability on audit delay. The study utilizes secondary data obtained from annual reports and audited financial statements of SOEs, which were accessed through the official IDX website and the respective companies’ websites. The results reveal that audit opinion and firm size have a significant influence on audit delay. Companies with unqualified opinions, larger firm size, and strong internal control systems tend to experience shorter audit completion times. Meanwhile, the size of the PAF—whether Big Four or non-Big Four—does not significantly affect the length of the audit process. Furthermore, profitability has a negative effect on audit delay, indicating that more profitable firms are likely to expedite the completion and publication of financial reports as a positive signal to investors and the market. These findings highlight the importance of internal corporate factors in accelerating the audit process and enhancing financial reporting transparency among Indonesian SOEs